Efek Anti-Hiperurisemia Kombinasi Ekstrak Eleutherine bulbosa dan Zingiber officinale pada Mencit Hiperurisemia - Rafli Bilal Firdizky; Noor Hujjatusnaini; Lilin Ika Nurindahsari (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to evaluate the effectiveness of the combined extracts of Eleutherine bulbosa and Zingiber officinale as an antihyperuricemic therapy in mice. The research employed a post-test only control group design with seven treatment groups, consisting of a negative control, a positive control (allopurinol), and five groups receiving different doses and ratios of the combined extracts. Uric acid levels were analyzed using a one-way ANOVA followed by Duncan’s multiple range test at a 5% significance level. The results showed that the combined extracts significantly reduced uric acid levels compared to the negative control, although no significant differences were observed among the combination groups. The combination dose of 300 mg/kg body weight with a 1:2 ratio produced a reduction in uric acid levels most comparable to the positive control. In conclusion, the combination of E. bulbosa and Z. officinale shows potential as an antihyperuricemic agent; however, further studies are required to explore the cellular mechanisms, pharmacokinetics, and related gene expression involved. Keywords: Eleutherine bulbosa, Hyperurisemia,Combination of Extracts, Zingiber officinale